Forms and Types of Neologisms in the Speech of Schizophrenia Patients - Reno Novita Sari; Ike Revita; Oktavianus Oktavianus (EDU-KATA, 2026)
This study aims to describe the forms and types of neologisms in the speech of schizophrenia patients. This study used a descriptive qualitative method with a psycholinguistic approach. The data were spontaneous spoken utterances produced by schizophrenia patients in daily communication at Dr. Soeharto Heerdjan Psychiatric Hospital Jakarta and Prof. HB Saanin Psychiatric Hospital Padang. The data were collected through observation, direct conversations with patients, and natural conversations among patients and those around them. All data were recorded and transcribed. The data were analyzed by identifying the forms and types of neologisms based on the theories of Fish and Covington et al. The results showed that 48 neologisms were found in the patients’ speech. Word forms were more dominant with 33 data (68.8%), while phrase forms were found in 15 data (31.2%). Based on the types, idiosyncratic word use was the most dominant type with 28 data (58.3%), while true neologism was found in 20 data (41.7%). The dominance of word forms indicates that patients tend to use simpler, more spontaneous utterances in daily communication. Meanwhile, the dominance of idiosyncratic word use shows that most neologisms still have connections with common language through sound similarity, word combinations, and recognizable language elements, although the meanings are personal. This study shows that neologisms are not only a form of language disorder but are also used by schizophrenia patients in everyday communication.